2014
DOI: 10.1016/j.anireprosci.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Novel SNPs in heat shock protein 70 gene and their association with sperm quality traits of Boer goats and Boer crosses

Abstract: The semen quality of bucks affects the reproduction performance of the herd and is influenced by genetic and non-genetic factors. Heat shock protein 70 (HSP70) is considered as an important gene affecting semen quality traits. The objectives of this study are to find single nucleotide polymorphisms in HSP70 coding region and their association with semen quality traits on Boer and Boer cross bucks. DNA isolated from 53 goats (36 pure South African Boer and 17 Boer crosses) was subjected to PCR amplification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 45 publications
3
20
0
1
Order By: Relevance
“…Moreover, a better characterization of all these proteins associated with sperm freezability differences would also aid in detecting proteins with a cryoprotective effect that could be incorporated into the freezing medium for enhancing sperm cryopreservation outcomes. Apart from variations in protein content, single nucleotide polymorphisms in different genes (e.g., HSP70 in buck sperm, PRNT in ram sperm and CFTR in bull sperm) have been correlated with inter-individual differences in sperm freezability [102][103][104]. Whether these genetic variations are the reason for the different protein profile of good and bad freezers still need to be elucidated.…”
Section: Molecular Mechanisms Involved In Those Factors That May Affementioning
confidence: 99%
“…Moreover, a better characterization of all these proteins associated with sperm freezability differences would also aid in detecting proteins with a cryoprotective effect that could be incorporated into the freezing medium for enhancing sperm cryopreservation outcomes. Apart from variations in protein content, single nucleotide polymorphisms in different genes (e.g., HSP70 in buck sperm, PRNT in ram sperm and CFTR in bull sperm) have been correlated with inter-individual differences in sperm freezability [102][103][104]. Whether these genetic variations are the reason for the different protein profile of good and bad freezers still need to be elucidated.…”
Section: Molecular Mechanisms Involved In Those Factors That May Affementioning
confidence: 99%
“…In addition to this, a landmark paper demonstrated that genomic differences existed between good and poor freezers in the sequences of polymorphism restriction fragments of 16 candidate genetic markers (Thurston et al 2002). This does not seem an exception for pigs, as a single-nucleotide polymorphism in the position 191 of HSP70, specifically C>G, has been found to provide better sperm quality at post-thawing in goats (Nikbin et al 2014).…”
Section: Freezability Markersmentioning
confidence: 99%
“…This does not seem an exception for pigs, as a single‐nucleotide polymorphism in the position 191 of HSP70, specifically C>G, has been found to provide better sperm quality at post‐thawing in goats (Nikbin et al. ).…”
Section: Freezability Markersmentioning
confidence: 99%
“…The heat shock protein 70 (hsp70), a heat shock protein ensures properly protein folding to fulfill their physiological functions, has been focused by several teams working on the goat, bull, boar, and fish semen and used it as a marker of good semen quality [57][58][59][60][61][62][63][64]. Hsp70 has been described to possess a protective effect on various types of injuries and some activities involved the Sirtuin/AMPK pathway [65].…”
Section: Discussionmentioning
confidence: 99%